EMOSI TOKOH DALAM NOVEL RUMAH HUJAN KARYA DEWI RIA UTARI (TINJAUAN PSIKOLOGI SASTRA) - Misye Audri; Christianto Syam; Antonius Totok Priyadi (Universitas Tanjungpura, 2022)
AbstractThis study aims to analyze the forms of emotion contained in the novel Rumah Rain by Dewi Ria Utari. Theories used in this study include: Emotions, types of emotions, novels, behavioristic psychology, learning literature in schools, and lesson plans. The method used in this study is a descriptive method with a qualitative research form that uses a behavioristic psychology approach. The data source used is the novel Home Rain by Dewi Ria Utari in the form of data on positive emotions and negative emotions in the form of quotes, words or sentences. The data collection technique used is in the form of a documentary study and the tools used are the researchers themselves. Techniques to test the validity of the data in the form of adequacy of references and triangulation. Furthermore, the data analysis technique used is in the form of content analysis. The results of this study about the emotions of the characters in the novel in the form of (1) positive emotions including happy emotions, amazed emotions, love emotions; (2) negative emotions include sad emotions, angry emotions, hate emotions, fear emotions, revenge emotions; (3) implementation of learning, namely designing lesson plans from the aspect of curriculum, learning objectives of literature, selection of teaching materials, and readability, learning media, learning approaches, and evaluation of learning.Keywords: Characters Emosian, Novel, Literature Psychology